Colorings of single-wall carbon nanotubes - Loyola, Mark (Archīum Ateneo, 2012)
In this work, we describe a process to classify and characterize nanotubes with several types of atoms by constructing colorings associated with single-wall carbon nanotubes. We also illustrate how colored single-wall carbon nanotubes can be used to model rolled-up versions of particular two-dimensional patterns such as carbon-boron nitride ternary graphite-like monolayers.